Meningkatkan Kepuasan Nasabah melalui Kualitas Pelayanan pada Koperasi Cipta Usaha Mandiri - Prasetiyo, Budi; Ndruru, Toni Krisman (Jurnal Pemberdayaan Ekonomi, 2024)
Purpose: The purpose of this research is to review customer satisfaction at the Cipta Usaha Mandiri Cooperative. Methodology/approach: This research applies a qualitative case study method using service quality to measure customer satisfaction at the Cipta Usaha Mandiri Cooperative. Results/findings: The results of the research and discussion show that one of the indicators of service quality is responsiveness, the importance of employees' willingness and ability to help customers and respond to their requests, so employees must serve customers quickly so that customers feel satisfied and if they are satisfied, customers will return for more information. use the services of the Cipta Usaha Mandiri Cooperative. One indicator of service quality is reliability which refers to discipline, the importance of time discipline in working to increase customer satisfaction because it can have a positive impact on customer satisfaction. If employees are disciplined on time when billing customers, the customer will certainly be ready to prepare funds to pay the bill, so that the customer will feel satisfied with the services at the Cipta Usaha Mandiri Cooperative. Limitation: The limitations of this research were that the research time was 3 month and the number of respondents was 20, which was considered insufficient. Contribution: Its contribution is to increase customer satisfaction and increase customer members.